TLC Profile of Methanol Extrac of Diospyros confertiflora Stem Bark - Syarpin Syarpin; Wahyu Nugroho (Jurnal Ilmiah Kanderang Tingang, 2020)
One of the large genus of plants growing in the Borneo forests is the genus Diospyros such as Diospyros siamang Bakh., Diospyros confertiflora (Hiern) Bakh., Diospyros areolata King and Gamble and Diospyros bornensis. Some of these plants are widely used by local people as medicinal purpose such as Diospyros borneensis as a medicine to treat panu by utilizing the bark and some other species have also been reported to have bioactivity as antioxidants, cosmetics, antidiabetes and hyperglukoma. In this study, Diospyros confertiflora bark was extracted by methanol. Then, the extract was evaluated using TLC to find out secondary metabolites content in Diospyros confertiflora. The TLC test showed that the methanol extract of diospyros confertiflora bark contains polar compounds and is predicted as a phenolate compound.